2021
DOI: 10.1002/ceas.12193
|View full text |Cite
|
Sign up to set email alerts
|

Faculty of Color's Mentorship Experiences in Counselor Education

Abstract: Attrition rates and professional advancement for faculty of color remain issues in CACREP‐accredited counseling programs. We interviewed 15 faculty of color regarding their perceptions of mentorship and the potential influence on retention and promotion. Findings include best practices for future mentorship models and implications for counselor education programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 30 publications
0
0
0
Order By: Relevance
“…Rather, the focus should be on mentorship that encourages dialogue between mentors and protégés, regarding their unique experiences, personalities, interests, and backgrounds (Hinton, Grim, & Howard-Hamilton, 2009). A study in the US within a Faculty of Counselling Education showed that for junior faculty of colour, mentorship was seen as an invaluable tool for retaining other faculty of colour; especially when formal mentoring relationships were developed between more senior and junior faculty members of colour (Oller, Lindo, Li, & Dan, 2021). This approach should be applied in STEM programs because the presence of racialized faculty and other students of colour, will empower more racialized youth to aspire to and stay in STEM programs.…”
Section: Policy Recommendationsmentioning
confidence: 99%
“…Rather, the focus should be on mentorship that encourages dialogue between mentors and protégés, regarding their unique experiences, personalities, interests, and backgrounds (Hinton, Grim, & Howard-Hamilton, 2009). A study in the US within a Faculty of Counselling Education showed that for junior faculty of colour, mentorship was seen as an invaluable tool for retaining other faculty of colour; especially when formal mentoring relationships were developed between more senior and junior faculty members of colour (Oller, Lindo, Li, & Dan, 2021). This approach should be applied in STEM programs because the presence of racialized faculty and other students of colour, will empower more racialized youth to aspire to and stay in STEM programs.…”
Section: Policy Recommendationsmentioning
confidence: 99%
“…Rather, the focus should be on mentorship that encourages dialogue between mentors and protégés, regarding their unique experiences, personalities, interests, and backgrounds (Hinton, Grim, & Howard-Hamilton, 2009). A study in the US within a Faculty of Counselling Education showed that for junior faculty of colour, mentorship was seen as an invaluable tool for retaining other faculty of colour; especially when formal mentoring relationships were developed between more senior and junior faculty members of colour (Oller, Lindo, Li, & Dan, 2021). This approach should be applied in STEM programs because the presence of racialized faculty and other students of colour, will empower more racialized youth to aspire to and stay in STEM programs.…”
Section: Policy Recommendationsmentioning
confidence: 99%